Cytokines and chemokines as biomarkers of community-acquired bacterial infection - Holub, Michal; Lawrence, David A; Andersen, Nancy; Davidová, Alžběta; Beran, Ondřej; Marešová, Vilma; Chalupa, Pavel (Mediators of inflammation, 2013)
Routinely used biomarkers of bacterial etiology of infection, such as C-reactive protein and procalcitonin, have limited usefulness for evaluation of infections since their expression is enhanced by a number of different conditions. Therefore, several inflammatory cytokines and chemokines were analyzed with sera from patients hospitalized for moderate bacterial and viral infectious diseases. In total, 57 subjects were enrolled: 21 patients with community-acquired bacterial infections, 26 patients with viral infections, and 10 healthy subjects (control cohorts). The laboratory analyses were performed using Luminex technology, and the following molecules were examined: IL-1Ra, IL-2, IL-4, IL-6, IL-8, TNF- α , INF- γ , MIP-1 β , and MCP-1. Bacterial etiology of infection was associated with significantly (P < 0.001) elevated serum concentrations of IL-1Ra, IL-2, IL-6, and TNF- α in comparison to levels observed in the sera of patients with viral infections. In the patients with bacterial infections, IL-1Ra and IL-8 demonstrated positive correlation with C-reactive protein, whereas, IL-1Ra, TNF- α , and MCP-1 correlated with procalcitonin. Furthermore, elevated levels of IL-1Ra, IL-6, and TNF- α decreased within 3 days of antibiotic therapy to levels observed in control subjects. The results show IL-1Ra as a potential useful biomarker of community-acquired bacterial infection.
Keywords: dospělí; Protein Precursors; Female; Cytokines; biologické markery; C-Reactive Protein; Interleukin-8; interleukin-4; Biomarkers; Adult; Calcitonin Gene-Related Peptide; ženské pohlaví; mladý dospělý; Calcitonin; Tumor Necrosis Factor-alpha; infekce získané v komunitě; interleukin-2; Adolescent; Bacterial Infections; cytokiny; Chemokines; lidé; Interleukin-2; Interleukin-6; Aged, 80 and over; proteinové prekurzory; Community-Acquired Infections; Humans; interleukin-8; Interleukin-4; TNF-alfa; Interleukin 1 Receptor Antagonist Protein; Male; Aged; Young Adult; interleukin-6; peptid spojený s genem pro kalcitonin; antagonista receptoru pro interleukin 1; chemokiny; lidé středního věku; C-reaktivní protein; senioři nad 80 let; kalcitonin; senioři; mužské pohlaví; Middle Aged; mladiství; bakteriální infekce